Conjugated polymer-based electrochromics: materials, device fabrication and application prospects. Issue 31 (15th July 2016) - Neo, Wei Teng; Ye, Qun; Chua, Soo-Jin; Xu, Jianwei
Abstract : The recent developments and trends of electrochromic conjugated polymers and their devices are highlighted in this review. Abstract : The research on electrochromic conjugated polymers (ECPs) and their devices has gone a long way. They can now perform with a multitude of color variations, high optical contrasts, rapid switching speeds and low power consumption. This review traces the progress of color control, synthetic methods, and the development of building blocks for ECPs. The advances in the integration and optimization of electrochromic devices (ECDs) in terms of their constituting components are presented. The potential of ECDs in numerous applications through the illustration of several prototypes is then highlighted. Finally, the challenges associated with the prospective commercialization of the said devices are discussed.